Heterologous Overexpression of Arabidopsis cel1 Enhances Grain Yield, Biomass and Early Maturity in Setaria viridis - Venkata, Bala P.; Polzin, Robert; Wilkes, Rebecca; Fearn, Armahni; Blumenthal, Dylan; Rohrbough, Sara; Taylor, Nigel J. (Frontiers in Plant Science, 2020)
Heterologous overexpression of Arabidopsis cellulase 1 (Atcel1) results in enhanced yield, early maturity, and increased biomass in dicotyledonous species like poplar and eucalyptus but has not been demonstrated in monocots. We produced transgenic Setaria viridis accession A10.1 plants overexpressing a monocotyledonous codon optimized (MCO) Atcel1. Agronomic characterization of the transgenic events showed that heterologous overexpression of MCOAtcel1 caused enhanced grain yield, shoot biomass, and accelerated maturation rate in the model grass species S. viridis under growth chamber conditions. The agronomic trait differences observed were consistent with previous reports in dicots but are here described in a monocot species and associated with increased seed yield. Overexpression of Atcel1 in S. viridis was shown to increase the number of panicles and seeds by 24-30%, enhance overall grain yield by up to 26%, and lead to a shoot dry biomass increase of 16-19%. Overexpression also reduced time to plant maturation and senescence by 12.5%. Our findings in S.viridis suggest that manipulation of Atcel1 has potential for developing early-maturing, higher-yielding, and monocotyledonous biomass crops suitable for climate-smart agriculture.